Evaluasi Kepuasan Pelanggan dalam Penggunaan Layanan Transjakarta Rute Kejaksaan Agung – Pulo Gadung, Jakarta - Kamal, Muhammad Mikail Yusuf; Sugiharto, Ega Rifdah; Salsabila, Nurus; Cahyati, Olivia Dwi (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2026)
Commuter behavior in the community around Jabodetabek causes the flow of population in big cities like Jakarta to become denser. This made the Jakarta provincial government take the initiative to create the Transjakarta program. Meanwhile, one of the busiest routes is corridor 4K which serves trips from the AGO Stop to Pulo Gadung Stop. The purpose of this research is to evaluate the extent of customer satisfaction in using Transjakarta route 4K services. This research uses a qualitative approach with in-depth interviews and observation as data collection methods. This research was conducted on Monday, June 30, 2025 and there were 5 informants, namely 2 students and 3 workers. The results showed that there were several successful evaluation indicators, such as the hotline number sticker, customer service friendliness, customer satisfaction level, and low cost. However, there are many indicators that cannot be said to be successful or even unsuccessful, such as the installation of CCTV, the quality of drivers, the comfort and cleanliness of facilities, the operation of TV displays, and the tap-in and tap-out machine payment system. This is a serious concern and can be used as a suggestion for the manager of Transjakarta corridor 4K in order to better manage Transjakarta 4K bus stops and buses.